Monitoring natural organic matter in drinking water treatment with photoelectrochemical oxygen demand - DeMont, Isobel; Anderson, Lindsay; Bennett, Jessica L.; Sfynia, Chrissa; Bjorndahl, Paul; Jarvis, Peter; Stoddart, Amina K.; Gagnon, Graham A. (American Water Works Association (AWWA), 2024)
Conventional metrics such as total organic carbon (TOC) and ultraviolet absorbance at 254 nm (UV254) may oversee aspects of natural organic matter (NOM) reactivity in drinking water treatment. The novel photoelectrochemical oxygen demand (peCOD) analyzer indirectly measures the oxygen consumed during NOM oxidation with photo- and electrochemical methods, quantifying NOM reactivity. peCOD was valuable for tracking NOM degradation in nine drinking water treatment facilities, particularly in processes where conventional metrics failed to capture changes in NOM from partial oxidation (e.g., biofiltration and oxidation). However, peCOD exhibited moderate correlations with TOC (R2 = 0.67) and UV254 (R2 = 0.48), indicating the need for its concurrent use with conventional methods. While peCOD was not a significant predictor of disinfection by-product formation potential (R2 < 0.20), its inclusion alongside standard NOM metrics improved the performance of multivariable regression models. Thus, peCOD provided a rapid, standardized, operator-friendly, environmentally conscious, concentration-based approach for evaluating NOM characteristics in drinking water samples.
Keywords: advanced treatment processes; drinking water treatment; natural organic matter; photoelectrochemical oxygen demand